Analisis Prinsip Nisbah dalam Pembiayaan Murabahah di Bank BSI KCP Lauser - Isna Maulida; Tuti Anggraini (UNIVED Press, 2022)
The phenomenon of murabahah financing is a contract based on buying and selling between the bank and the customer. Where the bank is the party that provides goods and sells them to customers by ordering goods to be purchased by customers. This study aims to examine and discuss the Indonesian Sharia Bank (BSI) KCP Lauser which estimates the profit earned so that it affects the ratio to be distributed. This study also discusses the ratio mechanism in murabahah financing at Bank Syariah Indonesia KCP Lauser. Then, discuss the implementation of the principles of profit-sharing ratio in murabahah financing by BSI KCP Lauser. The research method used is descriptive analysis method, which analyzes and presents facts about the implementation of the distribution of murabahah ratios carried out by Bank Syariah Indonesia KCP Lauser. This research was conducted to obtain primary sources of BSI KCP Lauser murabahah contract documents, murabahah financing tables and the results of interviews with the bank that performed the murabahah contract with the customer. The results of the study show that Bank Syariah Indonesia (BSI) KCP Lauser estimates the ratio to the bank's income, where the profit is based on the murabahah agreement agreed at the beginning of the agreement. Where the implementation is by buying and selling on murabahah, the bank will divide the margin. In general, the murabahah ratio at Bank Syariah Indonesia (BSI) KCP Lauser is appropriate because the provision of financing is based on a contract, the bank negotiates with the provider regarding the terms and conditions that will be used as the basis by the bank, the bank also makes an agreement with the customer. Then, BSI is also the executor of the offer, and on the date of delivery of assets the customer must submit a Murabahah Declaration, and the BANK will declare acceptance of the offer by signing the Murabahah Declaration and submitting it to the customer. Therefore, the ratio of Murabahah is very appropriate at BSI KCP Lauser. The murabahah financing mechanism at BSI KCP Lauser, the financing is not like conventional banks in general which lend money to customers. However, in this Islamic bank, according to customer needs.